(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the strategy for improving industrial structural changes in sustainable development of Khorezm region economy. The relevance of the research is determined by its correspondence to economic reforms being implemented in the country, comprehensive regional development programs, and priority directions of state policy for increasing industrial potential. Based on statistical data for 2010-2024 and regional comparative analysis, the dynamics of industrial development, territorial disparities, and existing opportunities have been identified. Statistical analysis, comparative analysis, and SWOT analysis methods were used in the research process. It has been established that the volume of industrial production in Khorezm region increased from 628.6 billion soums in 2010 to 21.5 trillion soums in 2023, representing a 34-fold growth. At the same time, it is shown that the region’s share in the republic’s industrial production remains low and there is a significant gap compared to industrial giants. Scientifically substantiated recommendations have been developed for effective use of industrial potential, improvement of investment environment, implementation of innovative technologies, and formation of industrial clusters. The research substantiates the role and significance of industrial structural changes in ensuring sustainable economic development of the region and defines strategic directions for improving the region’s industrial policy.